My Bookmark - Nik Ahmad Mazli, Nik Alya Batrisya; Daud, Nur Zahratul Jihad; Ahmad, Azree (Universiti Teknologi MARA, Kedah, 2017)
My Bookmark is to help readers pinpoint the exact location whitin a book up to the recent line and word in which they have read earlier. Generally, students or readers with the use of common bookmarks may easily spot the exact page which they have last read, but some may tend to forget which line or word they had stopped at. The My Bookmark design is an extended version of the common bookmarks since not only it could help book readers to find the marked page(s) but it could also help them to find the exact sentence or last word that they have read easily. This would then help readers to continue with their reading process smoothly.